Model CSR dalam Penguatan Modal Sosial dan Peran Kelembagaan Masyarakat - S. Suwandi; S. Sukaris; Abdurahman Faris (Akuntabilitas, 2019)
The issue of community independence is the central theme of national development which is the responsibility of all elements of the nation, including government, the private sector and any organization. Viewed from the government's point of view, this is clearly seen from the partisanship of empowerment policies and development through village funds that are very adequate to reach a developed and empowered village. The implementation or practice of corporate social responsibility has a direct influence on the role of community institutions and the role of community institutions directly influences the strengthening of community social capital. This community institution directly influences the improvement of community welfare and CSR programs must be able to increase community capacity for long-term activities (sustainable). The company must continue to encourage program recipients to have responsibility and ownership of the program implemented in order to strengthen social capital and the Company must implement a more concrete CSR program in increasing income economically because it is the main goal in the concept triple bottom CSR.